Pharmacological Correctors of Mutant CFTR Mistrafficking - Pedemonte, Nicoletta; Galietta, Luis (Frontiers in Pharmacology, 2012)
The lack of phenylalanine 508 (∆F508 mutation) in the CFTR Cl- channel represents the most frequent cause of cystic fibrosis (CF), a genetic disease affecting multiple organs such lung, pancreas, and liver. ∆F508 causes instability and misfolding of CFTR protein leading to early degradation in the endoplasmic reticulum and accelerated removal from the plasma membrane. Pharmacological correctors of mutant CFTR protein have been identified by high-throughput screening of large chemical libraries, by in silico docking of virtual compounds on CFTR structure models, or by using compounds that affect the whole proteome (e.g. histone deacetylase inhibitors) or a single CFTR-interacting protein. The presence of multiple defects caused at the CFTR protein level by ∆F508 mutation and the redundancy of quality control mechanisms detecting ∆F508-CFTR as a defective protein impose a ceiling to the maximal effect that a single compound (corrector) may obtain. Therefore, treatment of patients with the most frequent CF mutation may require the optimized combination of two drugs having additive or synergic effects.